The excretion study of a new derivative of 4,5-dihydroisoxazole-5-carboxamide - I. I. Yaichkov; M. K. Korsakov; N. N. Volkhin; V. E. Zaykova; O. E. Lasaraynz (Разработка и регистрация лекарственных средств)
Introduction. The new selective inhibitor of PAR-2 receptors, 3-(2-butyl-5-chloro-1H-imidazole-4-yl)-N-[4-methoxy-3-(trifluoromethyl)phenyl]-4,5-dihydro-1,2-oxazole-5-carboxamide (R004), is at the stage of preclinical trail. The excretion of R004 and its metabolites has not been studied before.Aim. Investigation of excretion of R004 and its metabolites in urine and feces after a single oral and intraperitoneal administration of substance.Materials and methods. The study was carried out on 2 groups of 6 Wistar rats. The R004 substance was administered orally to the first group at a dosage of 10 mg/kg, to the second group intraperitoneally at a dosage of 10 mg/kg. Biomaterial sampling was carried out with using metabolic cages. Urine was collected before administration of the drug and in the intervals of 0–4, 4–8, 8–12, 12–24, 24–48, 48–72, 72–96, 96–120 h after administration. Feces were collected before administration of the drug and in the intervals of 0–12, 12–24, 24–48, 48–72, 72–96, 96–120 h. The samples were analyzed using HPLC-MS/MS.Results and discussion. The analytical range of the urine quantification method for R004 and 4-methoxy-3-(trifluoromethyl) aniline (М2) was 5–2000 ng/ml, and 3-(2-butyl-5-chloro-1H-imidazole-4-yl)-4,5-dihydro-1,2-oxazole-5-carboxylic acid (M1) – 100–40 000 ng/ml. In feces concentrations of R004 were measured in the range of 0.5–500.0 µg/g, M1 – 4–4000 ng/g, M2 – 40–40 000 ng/g. The main part of the drug and metabolites was excreted within 48 h after administration. Complete elimination was achieved after 96 h. R004 is excreted unchanged only with feces: 94.83 ± 0.78 % after oral administration and 67.04 ± 0.59 % after intraperitoneal administration (M + m). The metabolite M1 is mainly excreted by renal route, the metabolite M2 is mainly excreted through intestine.Conclusion. Bioanalytical methods for determination of R004, M1 and M2 in urine and feces have been successfully validated. Most part of the R004 is eliminated unchanged by enteric route. M1 is excreted mainly in urine, M2 – mainly in feces.